How do you differentiate f(x)=cos3x^(1/3)f(x)=cos3x13 using the chain rule?

1 Answer
Jul 16, 2016

f'(x) = -(sin(3x^(1/3)))/(x^(2/3))

Explanation:

The chain rule for derivatives states that

d/dx[f(g(x))] = f'(g(x)) * g'(x)

In our case, we have

f(x) = cos(3x^(1/3))

Thus, by applying the chain rule, we get

f'(x) = d/dx[cos(3x^(1/3))] = -sin(3x^(1/3)) * 1/cancel(3) * cancel(3)x^(-2/3)

Simplifying this expression further yields

f'(x) = -sin(3x^(1/3)) * x^(-2/3)

= -(sin(3x^(1/3)))/(x^(2/3))